1984
DOI: 10.1002/j.1537-2197.1984.tb12545.x
|View full text |Cite
|
Sign up to set email alerts
|

Light and Electron Microscopy of the Resin Glands of Passiflora Foetida (Passifloraceae)

Abstract: Petiolar, bracteolar, and stipular glands from two varieties of Passiflora foetida were studied by both light and electron microscopy. These glands have previously been called nectaries. They do resemble the sugar‐secreting glands of other Passiflora species with respect to their location and morphology. However, cytological studies together with chemical tests of the exudate support the view that the glands in the varieties studied actually secrete a resin‐like substance which possibly functions as an anti‐he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0
2

Year Published

1984
1984
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 13 publications
1
23
0
2
Order By: Relevance
“…In colleters of Roupelia the process of senescence is initiated at the apex and proceeds basipetally. This is in accordance with the observations made in the resin glands of Passiflora by Durke et al (1984).…”
Section: Sc U Ss I O Nsupporting
confidence: 93%
See 1 more Smart Citation
“…In colleters of Roupelia the process of senescence is initiated at the apex and proceeds basipetally. This is in accordance with the observations made in the resin glands of Passiflora by Durke et al (1984).…”
Section: Sc U Ss I O Nsupporting
confidence: 93%
“…The association between crystals and extrafloral nectaries in Pithecellobium have be.m emphasized by Dave & Menon (1987). Durke et al (1984) also report the occurrence of crystal druses in the resin glands of Passiflora foetida. Unlike Aganosoma (Dave et al 1987), no hairs are found on the colleters in Roupelia.…”
Section: Sc U Ss I O Nmentioning
confidence: 90%
“…For example, the EFNs of Citharexylum mirianthum (Verbenaceae) produce lipids (S.R. Machado, unpublished results) and those of Passiflora foetida (Passifloraceae) also secrete lipids rather than sugars; so they are not 'nectaries' sensu stricto (Roth 1968;Durkee et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The possible coexistencc of a granulocrine and an eccrine secretion process is also suggested for Passiflora foetida resin glands (Durkee et al 1984).…”
mentioning
confidence: 99%